Determinants Of Tourist Decisions In West Bandung Within Indonesia’s Emerging Halal Tourism Policy Context - Amiludin, Amiludin; Ihsan, Hafiz Maulana; Maulida, De Lara Siti (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
Halal tourism, characterized by the provision of services and facilities that align with Islamic principles, such as halal cuisine, prayer facilities, and environments free of non-halal activities, has become a pertinent issue in business practices. This paradigm is increasingly gaining prominence in Indonesia, which is home to the world's largest Muslim population. In response to this development, the present research aims to investigate the impact of Islamic facilities, perceptions of pricing, and digital marketing strategies on tourists' travel decisions to West Bandung Regency. The collected data are subsequently synthesized into a central discussion of the potential of the halal tourism industry in this region. The findings indicate that Islamic facilities, price perception, and digital marketing efforts collectively exert a significant influence on tourists' decision-making processes in West Bandung Regency, as evidenced by an R² of 0.713. This implies that approximately 71.3% of the variance in tourist decisions can be attributed to these three variables. The results underscore the notion that tourists' choices are shaped through a complex interplay of spirituality, economic rationality, and the effectiveness of digital communication strategies. Consequently, integrating these three elements offers a comprehensive conceptual framework conducive to the development of sustainable halal tourism, representing a synthesis of Sharia-compliant values, consumer satisfaction, and responsiveness to the evolving dynamics of global tourism.